2020
DOI: 10.1002/ppul.25106
|View full text |Cite
|
Sign up to set email alerts
|

Is vitamin D deficiency a risk factor for COVID‐19 in children?

Abstract: Objective Coronavirus disease 2019 (COVID‐19) is a global health problem that can result in serious complications. The aim of this study was to investigate the prevalence and clinical importance of vitamin D deficiency in children with COVID‐19. Material and Methods This study includes 40 patients who were diagnosed to have COVID‐19 and hospitalized with the real‐time reverse transcription polymerase chain reaction method, 45 healthy matched control subjects with vitamin D levels. The age of admission, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(145 citation statements)
references
References 35 publications
11
112
0
7
Order By: Relevance
“…All studies, except for 2, included both male and female participants; in 1 study, participants were only male ( 30 ), and in another, only females were included ( 31 ). Nine studies were not included in the analysis because 4 of them were only descriptive [only reported concentration of 25(OH)D in patients; Supplemental Table 2 ] ( 31–34 ), 1 study was in children ( 35 ), and 4 were different in design from other studies [they assessed the effect of 25(OH)D 3 supplementation instead of 25(OH)D measurement] ( 14 , 36–38 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies, except for 2, included both male and female participants; in 1 study, participants were only male ( 30 ), and in another, only females were included ( 31 ). Nine studies were not included in the analysis because 4 of them were only descriptive [only reported concentration of 25(OH)D in patients; Supplemental Table 2 ] ( 31–34 ), 1 study was in children ( 35 ), and 4 were different in design from other studies [they assessed the effect of 25(OH)D 3 supplementation instead of 25(OH)D measurement] ( 14 , 36–38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ye et al also revealed that VDD was a risk factor for COVID-19, especially for severe/critical cases (31). Moreover, other studies showed a lower vitamin D level in COVID-19 patients than the control group (20,21,26). A study done in Saudi Arabia found that 74.7% of COVID-19 patients had VDD and they were 7 times at risk of mortality [HR 7.0 (CI 1.7-28.2); p = 0.007] (28).…”
Section: Results Of Individual Studiesmentioning
confidence: 94%
“…The sample size of the studies ranged from 134 to 79,381. The studies were conducted in Europe (14,(20)(21)(22)(23)(24)(25), America (26,27), and Asia (28)(29)(30)(31)(32). Moreover, the studies were cohort studies (14,22,25,27,30), case-control studies (20,21,26,31,32), cross-sectional studies (23,28,29) and interim audit (24) (see Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In Table 1B , we report findings from 21 studies in which 25(OH)D levels were measured in individuals hospitalized for COVID-19 or after confirmed positive test for SARS-CoV-2 (via PCR) ( Table 1B ). Eleven of these studies reported significantly lower 25(OH)D levels for those with COVID-19 or who were positive for SARS-CoV-2 infection compared to control groups ( 204 , 205 , 207 – 209 , 211 , 212 , 214 , 218 , 219 , 223 ). Many of these studies were limited by their small sample size, a lack of clarity on what assay was used to measure 25(OH)D, and that 25(OH)D levels were not measured before infection was diagnosed.…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%